Thieme Chemistry Journal Awardees - Where Are They Now? Synthesis of (-)-Cubebol by Intramolecular Cyclopropanation of a Terminal Epoxide - Hodgson, D; Salik, S (2009)
A synthesis of (-)-cubebol from l-menthone is described. The key step involves efficient (90%) and completely stereocontrolled intramolecular cyclopropanation of an unsaturated α-lithiated terminal epoxide. © Georg Thieme Verlag Stuttgart.